Pengaruh Capital Adequacy Ratio dan Non Performing Loan terhadap Jumlah Penyaluran Kredit Di Kota Denpasar - Astuti, I Gusti Agung Ayu Ngurah; Suartina, I Wayan; Wina Premayani, Ni Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the effect of CAR and NPL on the amount of credit disbursement at Rural Banks in Denpasar City. The method of collecting data in this research was carried out by observation where the researcher was not directly involved. Observations were carried out over a 4 year period, namely the 2019-2022 period on 23 Rural Banks in Denpasar City and then analyzed using multiple linear regression, determination, t test and F test. The results of this research are that the capital adequacy ratio (CAR) has a positive and significant effect on the amount of credit disbursement to BPRs in Denpasar City. Non-Performing Loans (NPL) have a negative effect on the amount of credit disbursement to BPRs in Denpasar City. Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) simultaneously have a positive and significant effect on the amount of credit disbursement to BPRs in Denpasar City. Suggestions that can be made in this research are that future researchers are expected to be able to develop this research by including or increasing the number of variables that can influence the amount of credit disbursement, such as the number of customers and trust in customers.